Biology and parasites of Pteronotus gymnonotus from the Caatinga shrublands of Ceará (Brazil) - Pereira da Silva, Shirley Seixas; Guedes, Patricia Gonçalves; Severino, Flávia Silva; Almeida, Juliana Cardoso (THERYA, 2023)
Mormoopid bats are distributed from southern United States of America to Brazil and comprise the genera Mormoops and Pteronotus. Although forms of Mormoops in Bahia, Brazil were described for the Quaternary, only some of the extant species of Pteronotus occur in this country, including P. gymnonotus. The species distribution ranges from southeastern México to northeastern Bolivia and central Brazil. This work presents information about food preference, reproduction, and the ectoparasitological fauna of P. gymnonotus in the state of Ceará. Fieldwork took place over ten consecutive days in the rain and dry seasons, in 2000, 2012, 2013, and 2019, on trails within the Serra das Almas Private Natural Heritage Reserve. A total of 14 P. gymnonotus specimens were caught in the three main phytophysiognomies present in the region. They were inspected for ecto and endoparasites, and fecal material was collected and analyzed under a light microscope. Of the total collected females, four were pregnant and one was lactating in January, during the rain season. No food residues or evidence of endoparasites were observed in the gastric content of the animals. Regarding the fecal samples, fragments of insects were found and identified as belonging to the orders Coleoptera and Lepidoptera. Seven individuals were infested with ectoparasites of the subfamily Acari and newly described associations with Diptera genera are presented. Due to the scarcity of data about these bats in the Caatinga biome, data reported here help explain the ecological interactions of P. gymnonotus in this semiarid area in Brazil.